The Middle East and the European Common Market - Ramazani, Rouhollah K. (Charlottesville : University Press of Virginia, 1964)
This study is concerned with the impact of the common market on the Middle East and the reaction of that area to the community.
Bibliographical footnotes.
osc 29/08/2018
Loans
Keywords: Economic integration; Middle East